Localised treatment and 6-month outcomes in patients with cytomegalovirus retinitis at a tertiary ophthalmology service in Ga-Rankuwa - Fatima Laher; Claire Cullen; J Baile Matlala (AOSIS, 2012)
Objective. There are few data from before the antiretroviral therapy (ART) era for cytomegalovirus retinitis (CMV-R) from settings where cost limits use of systemic treatment. This study examines CMV-R treatment and survival outcomes in a public hospital ophthalmology service in Ga-Rankuwa, South Africa. Methods. From October 2009 to October 2010, voluntarily consenting participants over the age of 15 years with incident clinically diagnosed CMV-R seen at the Dr George Mukhari Hospital ophthalmology clinic were prospectively enrolled in an observational study. Treatment was per clinic protocols and patients were followed up with structured data collection for up to 6 months. Results. Eight individuals, all HIV infected and 50% female, were identified and enrolled. At enrolment, median age was 38 years (interquartile range (IQR) 32 - 39 years), median CD4 count 20 cells/μl (IQR 13 - 46.5 cells/μl), and 50% were currently receiving ART (mean duration of ART use 18 days, standard deviation (SD) 2.99 days). No participant received systemic ganciclovir, but 6 reported symptom combinations suggesting systemic CMV: shortness of breath (n=3), diarrhoea (n=3) and/or central nervous system complaints (n=3). Ten eyes had visual impairment less than counting fingers at enrolment. Treatment combinations were: ART plus intravitreal ganciclovir (n=5), intravitreal ganciclovir alone (n=2), and ART alone (n=1). Six-month outcomes were: death (n=1), survival (n=6), loss to follow-up (n=3), untraceable (n=1), systemic symptom resolution (4/4), visual acuity deterioration (0/5), and persisting uveitis (2/3). Conclusion. In the ART era, incident CMV-R appears to be uncommon in this setting. CMV-R may occur within the first 3 weeks after ART initiation. Even in CMV-R patients with suggestive systemic symptoms, 6-month survival is good despite no systemic CMV therapy. S Afr J HIV Med 2012;13(2):68-71.